Anorectal Malformations (ARM) : The Hospital Universiti Sains Malaysia (HUSM) experience from 1999 to 2006 - Malapan, Kirubakaran (2007)
Anorectal Malformations (ARM) are a complex group of malformations diagnosed at the time of birth because of absence or an ectopic location of anus. The usual rep01ted incidence is between l per 1500 and 1 per 5000 live births and they are more often seen in boys than in girls. The incidence of associated organ anomalies with ARM is variously reported from 20% -70% some being minor anomalies but others being life threatening. Further management depends on the sex of the patient, type of malformation either high or low and the associated anomalies. All operative procedures for the correction of ARM aim at providing portal for the discharge of feces from the perineum and establishing a working relationship between the bowel and sphincter. The aim of the study is to review the patients presenting with anorectal malf01mations (ARM) to Hospital Universiti Sains Malaysia (HUSM) and describe the demographics and outcome in relation to the type of ARM. The study was a retrospective case review which was canied out in the Paediatric Surgery Unit, Depa1iment of Surgery, Hospital Universiti Sains Malaysia (HUSM) between January 1999 and January 2006. The case notes and operative notes were screened for epidemiological data and data relevant to the study. Patients diagnosed with ARM but did not undergo surgery, and patients whose case notes could not be traced or incomplete were excluded from the study. All the data entry and analysis were carried out using the social science and statistical packaged (SPSS) version 12 licensed to USM. A p value of less than 0.05 was considered statistically significant. Ninety eight patients were included into the study after fulfilling the inclusion criteria. The male to female ratio was 2 to 1 and 97% of the patients were Malays. The birth weight of the patients in this study ranged from l.3kg to 4.5kg. Forty two point eight percent of the patients presented to HUSM within the first day of life. The most common presenting symptoms were abnonnal passage of meconium (39.7%), abdominal distension ( 15.3%) and constipation (5.1 %). The investigative procedures done to detect associated anomalies were ultrasound abdomen (94.8%), babygram (87.7%) and echocardiogram (75.5%). Associated anomalies were detected in 56.6% of the patients. The most number of associated anomalies detected in patients with ARM was cardiovascular anomalies (25.5%) followed by urological anomalies (22.4%) and chromosomal anomalies (17.3%). Fifty two patients (53%) underwent surgical repair for low ARM which were mini PSARP (69.2%) followed by anoplasty (25%) and anal shift (5.8%). Forty six patients (46.9%) underwent surgery for high ARM of which only 2% underwent single stage PSARP repair. Forty four patients (73.3%) who had colostomy formed were later diagnosed with high type of ARM. The remaining 16 patients who had colostomy formed were diagnosed with low ARM (26.7%). Post operative complications were similar to those reported in earlier studies. In this study, there were 46 patients (46.9%) with high type of ARM and 52 patients (53 .1 %) with low type of ARM. Only 44 patients were able to be contacted and interviewed to assess their functional outcomes. Anal stricture was a significant complication in patients who were not compliant with the anal dilatation protocol (p = 0.007). Patients with low ARM were noted to have more adequate weight gain as compared to high ARM patients (p=0.002). The incidence of constipation was higher among patients with low ARM and this was highly significant (p= 0.000). However, the incidence of soiling and incontinence was higher among patients with high ARM (p=O.OOO). Seven patients achieved full continence at follow up and they were all males (p=0.048). Only 7 patients in our study achieved "good" outcome following surgery, 54 patients achieved "fair" outcome and 16 patients had "poor" outcome. The mortality rate after definitive surgery in this study was 4%. The demographic finding in the study is quite similar to those published in the literature from other parts of the world. The clinical diagnosis of type of ARM was accurate in 76.8% of the patients and it was more difficult in making a diagnosis of high ARM clinically, compared to low ARM. The high incidence of associated anomalies in our study makes careful clinical examination and evaluation during the neonatal and early infantile period mandatory in all cases of ARM. Anal dilatations are a vital part of the postoperative management to avoid stricture at the anoplasty site. The low number of patients with good outcome in our study suggests that more attempts must be made to keep these patients on follow up, with the development of a proper bowel management program and an integrated team approach to achieve better outcomes.